MEMBANGUN GOLDEN GENERATION MELALUI PEMBELAJARAN PAI TERPADU DI SMP YPSA MEDAN - Imran Siregar (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
This paper draws on a study on Integrated Religious Education for School Education System conducted in 2013 focusing on Junior Secondary Education of Yayasan Pendidikan Shafi yyatul Amaliyyah (SMP YPSA) in Medan, using a qualitative approach comprising in-depth interviews with key informants, such as the foundation chairman, Principal, Islamic subject teachers, and the parents. This study focused on the development of Islamic Subjects (PAI) management integrated with the rest of junior high school education activities in SMP YPSA Medan. This study found that integrated PAI in the SMP YPSA Medan was implemented by integrating religious and character values into non-religious subject matters. Islamic subjects and character building here were considered the soul of all subject matters. Such integration model was applied in cobwebs construction as well as a logical consequence of YPSA vision and mission that determined that Islamic subjects and character building would be the characteristics of SMP YPSA Medan.